Benedict's Monastic Theological Formation: A Garden of Nuts - Davis, Thomas X. (Cistercian studies quarterly, 2011)
The article focuses on several writings made as reference by Pope Benedict XVI on the distinction between scholastic theology and monastic theology during his public talk in Saint Peter's Square in Vatican City on October 28 and November 4, 2009. It states that Dom Jean Leclercq's article partitions theology on the basis of its milieu, such as monastic cloisters. Moreover, article by Dom Adalbert de Vogüé provides monastic formation in the context of lectio divina.